Optimal design of leaf springs for vehicle suspensions under cyclic conditions (2022)
The suspension systems are designed to provide good performance in terms of comfort and maneuverability and to satisfy other requirements such as fatigue strength. This study focuses on the leaf springs, a classic mechanism; leaf springs are still being extensively used in several types of vehicles because of their high load capacity and low manufacturing and maintenance costs. Its dynamic behavior assesses stationary nonlinear preload state components to provide considerable added value to this suspension type. This assessment considers the contact condition of the suspension’s components and the large deflections and tightening torques observed in the whole assembly. Furthermore, the components of the non-suspended mass subsystems, such as tires, shock absorbers, and stabilizer bars, are characterized according to the simplified models for reducing their computational cost. In addition, a commercial test vehicle is used for simulating the complete system using three-dimensional modeling for describing its most relevant components in terms of their mass and rigid connection. The vehicle is additionally analyzed using multibody system simulations (MBS) coupled with the finite element method (FEM) in an implicit nonlinear transient environment using the ANSYS APDL solver. This dynamic simulation is parameter-driven for obtaining the experimental design and determining the optimal suspension stiffness and damping features required for transporting suitable load sizes.